VOLUME CHANGE OF CLAYS INDUCED BY HEATING AS OBSERVED IN CONSOLIDATION TESTS - TOWHATA, IKUO; KUNTIWATTANAKU, PISIT; SEKO, ICHIRO; OHISHI, KANTA (SOILS AND FOUNDATIONS, 1993)
Laboratory tests were conducted to investigate the volume change of clays induced by elevated temperature. A coventional consolidometer equipped with a heater and a thermostat was employed for a study on the interaction between clay particles and pore water. Consolidation tests on normally consolidated specimens revealed volume contraction upon heating and, when stress application continued further, the samples behaved like overconsolidated clays. Volume contraction occurred similarly, when a sample in the course of secondary compression was heated. Although reloading overconsolidated samples showed similar volume change as well, samples during stress reduction swelled in contrast. Finally, an attempt was made to propose a hypothesis that could explain the mechanism of thermal volume change of clays as observed in the present study.